Pilates for elderly women: An improvement in functional mobility and balance - Honório, Samuel (2019)
This study intends to determine and relate the effects of a program of Pilates sessions in elderly women, comparing balance assessments by the Berg scale and physical mobility with the scale of Leighton for articular ampleness. Elderly evaluation was conducted by using a universal goniometer, the Berg scale, the Leighton scale and data collection was performed in two different moments. This study had 52 elderly women aged between 60 and 83 years. The participants had Pilates sessions of 30 minutes each, twice a week, for 6 months. The statistical analysis used were descriptive based on mean and standard deviation, statistical inference by applying the Wilcoxon and the effect size by Cohen’s d where we observed an increase in balance parameters and articular mobility of elderly practitioners, with improvements from considered “average” in the first evaluation to “above average” in the second evaluation. The implemented Pilates program proved to be extremely favourable, with significant improvements in all analysed variables with intermediate and large effect sizes.